KAJIAN KAPASITAS RUANG TUNGGU KEBERANGKATAN DOMESTIK DI BANDAR UDARA INTERNASIONAL SULTAN SYARIF KASIM II PEKANBARU - Dien Amalia Putri; Satiti Utami; Kardi (Politeknik Penerbangan Indonesia Curug, 2019)
Increasing the number of passengers every year and the limited capacity of the waiting room will affect the comfort level of service users, especially in the domestic departure lounge of Sultan Syarif Kasim II Pekanbaru Airport. During peak hours between 2:00 p.m. and 3:00 p.m. WIB, the density of passengers in the waiting room for domestic departures is seen. The piled up flight schedule adds to the density of the waiting room. In addition, many passengers who are standing and passenger space are uncomfortable, this is related to the capacity of the waiting room and the area of the waiting room per passenger. For this reason, the management of Pekanbaru's Sultan Syarif Kasim II Airport needs to increase the capacity of domestic departure waiting rooms through the addition of additional space or the addition of waiting rooms and facilities to support activities in the waiting room at present. The use of international departure waiting rooms can also be an alternative to accommodate departing (domestic) passengers during rush hour so that the density in the domestic departure lounge can be reduced. With this research, it is expected that the manager of Pekanbaru Sultan Syarif Kasim II Airport can realize a comfortable departure lounge atmosphere in accordance with service level standards in accordance with the Director General of Civil Aviation Decree Number: SKEP 347 / XII / 1999 concerning Design Build and / or Engineering Airport Facilities and Equipment as well as the Minister of Transportation Regulation of the Republic of Indonesia Number PM 178 of 2015 concerning Standards for Airport Service Users.